Multi-omics investigation of high-transglutaminase production mechanisms in Streptomyces mobaraensis and co-culture-enhanced fermentation strategies - Chang, Huanan; Zheng, Ziyu; Li, Hao; Xu, Yanqiu; Zhen, Gengyao; Zhang, Yao; Ren, Xidong; Liu, Xinli; Zhu, Deqiang (Frontiers in Microbiology, 2025)
Transglutaminase (TGase) has been widely applied in the food industry. However, achieving high-yield TGase production remains a challenge, limiting its broader industrial application. In this study, a high-yield strain with stable genetic traits was obtained through UV-ARTP combined mutagenesis, achieving a maximum TGase activity of 13.77 U/mL, representing a 92.43% increase. Using this strain as a forward mutation gene pool, comparative genomic research identified 95 mutated genes, which were mostly due to base substitutions that led to changes in codon usage preference. Transcriptomic analysis revealed significant expression changes in 470 genes, with 232 upregulated and 238 downregulated genes. By investigating potential key regulatory factors, comprehensive analysis indicated that changes in codon usage preference, amino acid metabolism, carbon metabolism, protein export processes, TGase activation, and spore production pathways collectively contributed to the enhancement of TGase activity. Subsequently, the in vitro activation efficiency of TGase was further improved using co-cultivation techniques with neutral proteases secreted by Bacillus amyloliquefaciens CICC10888, and a TGase activity of 16.91 U/mL was achieved, accounting for a 22.71% increase. This study provides a comprehensive understanding of the mechanisms underlying high-yield TGase production and valuable insights and data references for future research.